Relation of career services and career uncertainty at secondary school (Training and Practice : Journal of Educational Sciences, 2021)
Numerous researches highlighted (Mahasneh és Farajat, 2015, Török, 2016, Antonellou és Kounenou, 2016, Maree, 2019) that special career education and/or interventions make positive effect on students’ career decision and commitment. In our research we have explored the relationship among career education services and career uncertainty. We have found no correlations between the level of uncertainty and the number of services. Rather, there is a difference among grades and gender in terms of self-knowledge and only between gender in terms of anxiety and uncertainty factors as well. The highlighted phenomena are in significant relation with the factor of career information. In our interpretation it is important for students to get information about each profession in order to increase their self-knowledge and soothe the negative effect of uncertainty, but according to our sample school career education does not satisfy this need.